INSTITUTIONAL GOVERNANCE IMMIGRATION TRANSFORMATION TOWARDS GOOD GOVERNANCE IN INDONESIA: SROI ANALYSIS - Andaryadi, Sandi; Setyawan, Sigit; Nurdin, Ismail (Polteknik Imigrasi, 2024)
Immigration institutional governance is very important in the development of an organization, especially towards good governance. This is also relevant in public services which require change and renewal of an organization as well as increasing state revenue. So this research will be very important by using SROI to see the impact on social, environmental and economic values ​​for society and the impact on foreign investment in Indonesia. The research method used in this research is a literature review with emphasis on several scientific articles and relevant sources. The research results show that the social, environmental and economic values ​​of immigration provide many benefits for the country and for organizations in their development that contribute to the country and society.